Effects of alternaria leaf spot (alternaria alternata (fr.) keissi) on the growth, yield and phytochemical profile of moringa oleifera lam - Mnisi, Faith (My University, 2024)
Moringa oleifera is a species of Moringa belonging to the family Moringaceae which has been used for thousands of years in less developed communities. It is a nutrient rich plant containing a variety of minerals and phytochemicals. Moringa is affected by pests and diseases which affect their growth, yield and phytochemical composition. Alternaria alternata is one of the pathogens that causes Alternaria leaf spot disease in Moringa. The objective of the study was to determine whether Alternaria leaf spot (caused by Alternaria alternata) affects the growth, yield and phytochemical contents of the PKM1 cultivar of M. oleifera. The study was conducted at the University of Limpopo, Plant Pathology Laboratory, and the Green Biotechnologies Research Centre of Excellence. Two main treatments: M. oleifera seedlings inoculated with A. alternata and a non-inoculated control were used. The data collected for growth parameters were plant height and stem diameter. Fresh shoot mass and root length were collected as yield parameters. For the physiological attributes: photosynthetic rate, stomatal conductance, transpirationrate, water use efficiency, and Ci intercellular CO2 concentration were collected. The L*, a*,b*,c* and h values were collected as colour parameters. Lastly, the biochemical compounds (total flavonoids, total phenols, antioxidant activity and chlorophyll). To compare differences in treatment means, paired sample t-test was performed at a 5% significance level using Sigma Stat software 2016 and Graph Prism 5. The inoculated treatment significantly (p<0.05) reduced the plant height and fresh shoot mass and had no significant (p>0.05) effect on the stem diameter and root weight Inoculation affected the physiological attributes as follows: photosynthetic rate, stomatal conductance and transpiration rate was decreased by 4%, 17% and 4% respectively, while the water use efficiency increased by 10% in comparison to the non-inoculated plants. There was no significant effect on the Ci intercellular CO2 concentration. The colour parameters affected by the treatment were as follows: the mean± standard error of the treatment was higher than the control for the L*, a*, b* and c* values. There was no significant difference for the h value. The inoculation significantly (p<0.05) increased the total flavonoids, phenols and antioxidant activity by 69%, 4% and 4% and decreased, chla, chlb and totchl by, 48%, 43% and 44% respectively. In conclusion, the introduction of A. alternata into PKMI cultivar of M. oleifera influenced its growth and development and altered the physiological and biochemical defence mechanism
Thesis (M. Sc. Agriculture (Plant Production)) -- University of Limpopo, 2024
Keywords: Moringaceae; Moringa; Alternaria leaf spot; Alternaria; Moringa oleifera; Moringaceae